Probability of cardiovascular disease and assessing the relationship of job stress on cvd risk: a study among primary healthcare providers in Kelantan using the Framingham and Globorisk scores - Aziz, Wira Alfatah Ab Ayah @ Ab (2020)
Cardiovascular disease (CVD) remains the leading cause of mortality worldwide. Therefore, many researchers developed prediction models for CVD for early risk identification. On the other hand, numerous studies already demonstrated the detrimental effect of job stress on CVD, which often becomes the disease's neglected risk factor due to its complexity in measurement. Due to a challenging working environment, particularly in health sectors, a well-structured study was carried out to determine the relationship between job stress and CVD among primary healthcare workers in Kelantan. This study aimed to describe the 10-year probability of CVD risk and the stratification of CVD risk among primary healthcare providers in Kelantan by using the established and the newly developed CVD prediction model to determine the performance of the newly developed CVD model compared to the established one, to determine the proportion of job stress among them and finally to estimate the job stress as the predictive factor for CVD among them. This study was conducted among primary healthcare providers (HCPs) aged 40 and above at all Kelantan districts. This study period was about six months, from March 2019 until August 2019, comprising primary and secondary data collection. Ten variables were required for CVD prediction for The General Framingham CVD Model and Globorisk Model, namely age, gender, systolic blood pressure, diabetic status, smoking status, treatment status of hypertension, height, weight, total cholesterol level and high-density lipoprotein cholesterol level. The data was retrieved from the offline regular medical database (RME-40) from the district level's occupational health unit. By using the models, the CVD risk was classified into low, medium and high. self-administered validated Malay version questionnaire (M-JCQ) was distributed to the selected participant who fulfilled the study criteria for identifying the HCPs with job stress. The score of the main three scales from M-JCQ, namely decision latitude, psychological job demand and social support, were calculated according to the given formula by JCQ (copyrighted) to classify the primary HCPs into four groups, namely Karasek strain category; high job strain, low job strain, passive and active. High job strain was defined as job stress according to the guideline by JCQ. Descriptive analysis, Cohen Kappa agreement analysis, Bland-Altman analysis, Chi-square, and linear regression were employed to analyze the data. CVD prediction models revealed the low-risk group for CVD ranging from 78 to 85% and the high group from 1% to 4% of the total HCPs. For categorical agreement, The Globorisk Office and The General Framingham CVD BMI showed good agreement with Kappa value of 0.628 ± 0.078 compared The Globorisk Lab and The General Framingham CVD Lipid (Kappa value = 0.624 ± 0.12). Bland-Altman plots further supported the model agreement of both CVD prediction models. About 145 (28.5%) HCPs identified with job stress. A stratified analysis demonstrated the professional group (Degree and above) has the highest proportion of job stress (41.2%), and the diploma group has the lowest proportion of job stress among the four job qualification groups (22.9 %).